Five-year dynamics adrenergic reactivity of erythrocytes after radio-frequency sympathic denervation of renal arteries in patients with resistant arterial hypertension - Tatiana Yu. Rebrova; Alla Yu. Falkovskaya; Sergei A. Afanasiev; Viktor Fedorovich Mordovin; Irina Vladimirovna Zyubanova; Elvira Faritovna Muslimova (Терапевтический архив, 2023)
Aim. To study the initial state of adrenergic reactivity and the five-year dynamics of the beta-adrenergic reactivity index of erythrocyte membranes and the manifestation of the antihypertensive effect of the procedure for radiofrequency destruction of sympathetic structures of the renal artery in patients with resistant arterial hypertension.